2014
DOI: 10.1590/0004-282x20130189
|View full text |Cite
|
Sign up to set email alerts
|

Effects of botulinum toxin type A for spastic foot in post-stroke patients enrolled in a rehabilitation program

Abstract: The objective of this study was to evaluate the effects of botulinum toxin type A (BTX-A) on spastic foot in stroke patients in a rehabilitation program. Method: Hemiparetic stroke patients (n=21) enrolled in a rehabilitation program were divided into two groups. The first group (n=11) received a total of 300UI BTX-A, and the second group (n=10) received 100 UI BTX-A. All patients were assessed at baseline and 2, 4, 8 and 12 weeks after injection for Modified Ashworth Score, time walking 10 meters, and the Fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Twenty-six studies were reviewed, including 1307 patients. There was a significant effect observed in 23 studies in the intervention group on spasticity [18][19][20][21][22][24][25][26][27][28][29][30][31][32][34][35][36][37][40][41][42][43][44][45]. In regard to upper limb motor function, 11 of 14 cases showed improvement, but two studies showed significant differences in comparison with the control group [19][20][21]25,[27][28][29][30][31][32][33][34]37,42,45].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Twenty-six studies were reviewed, including 1307 patients. There was a significant effect observed in 23 studies in the intervention group on spasticity [18][19][20][21][22][24][25][26][27][28][29][30][31][32][34][35][36][37][40][41][42][43][44][45]. In regard to upper limb motor function, 11 of 14 cases showed improvement, but two studies showed significant differences in comparison with the control group [19][20][21]25,[27][28][29][30][31][32][33][34]37,42,45].…”
Section: Discussionmentioning
confidence: 99%
“…In regard to upper limb motor function, 11 of 14 cases showed improvement, but two studies showed significant differences in comparison with the control group [19][20][21]25,[27][28][29][30][31][32][33][34]37,42,45]. In regard to lower extremity motor function, 12 of 14 cases showed improvement, and seven studies showed a significant difference in comparison to the control group [18,19,[22][23][24][25][26]35,36,[38][39][40][41]43,44].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations